Immune regulation and emerging roles of noncoding RNAs in Mycobacterium tuberculosis infection - Liang, Shufan; Ma, Jiechao; Gong, Hanlin; Shao, Jun; Li, Jingwei; Zhan, Yuejuan; Wang, Zhoufeng; Wang, Chengdi; Li, Weimin (Frontiers in Immunology, 2022)
Tuberculosis, caused by Mycobacterium tuberculosis, engenders an onerous burden on public hygiene. Congenital and adaptive immunity in the human body act as robust defenses against the pathogen. However, in coevolution with humans, this microbe has gained multiple lines of mechanisms to circumvent the immune response to sustain its intracellular persistence and long-term survival inside a host. Moreover, emerging evidence has revealed that this stealthy bacterium can alter the expression of demic non-coding RNAs (ncRNAs), leading to dysregulated biological processes subsequently, which may be the rationale behind the pathogenesis of tuberculosis. Meanwhile, the differential accumulation in clinical samples endows them with the capacity to be indicators in the time of tuberculosis suffering. In this article, we reviewed the nearest insights into the impact of ncRNAs during Mycobacterium tuberculosis infection as realized via immune response modulation and their potential as biomarkers for the diagnosis, drug resistance identification, treatment evaluation, and adverse drug reactions prediction of tuberculosis, aiming to inspire novel and precise therapy development to combat this pathogen in the future.